Microstructure and wear behavior of arc thermal sprayed base-cutter blades in sugarcane harvesters - Chuleeporn Paa-rai; Nuchira Dejang (Songklanakarin Journal of Science and Technology (SJST))
Base-cutter blades operate close to the soil during sugarcane harvesting, causing a high wear rate. The present study aims to improve the wear resistance of the blades with an economical surface treatment, so wire arc thermal spray was applied with two alternative types of cored wires, namely chrome nickel amorphous (AM) and titanium tungsten carbide (TiW). The microstructure study showed that AM coating contained an amorphous structure, while the TiW coating appeared to have a relatively non-homogeneous structure containing W and Ti carbide dispersion resulting in a higher hardness (876.40 HV0.1) than that of AM coating (814.48 HV0.1). However, after dry sand rubber testing, the AM coating exhibited nearly 2 times lower wear rate than that of the uncoated base-cutter blades or TiW coated ones. Therefore, the arc sprayed AM coating can be an economical approach to extend the service life of the blades.